Value Addition of non-timber forest products and other tribal products - Rohini, A; Selvi, M Padma; Anjugam, M (Indian Farming, 2017)
Imparting training, providing market intelligence, establishinglinkages with financial institutions, providing managerial inputs is theneed of the hour for the livelihood development of tribal populationwho depend on NTFPs and other minor forest products.